Pembelajaran Bahasa Arab Dalam Buku Teori Dasar Nahwu & Sharf Tingkat Pemula Karya Dr. H. Abdul Haris, M.Ag. (Telaah Aspek Materi Ajar & Teknik Penyajian) - Putri Ladya Rausyan Fikri; Fatkhurrohman (SPESIFIK: Jurnal Pendidikan dan Pembelajaran, 2024)
Learning Arabic in Indonesia faces several problems, such as lack of student preparation, complexity of the material, and lack of teacher ability in developing teaching materials. One important component is learning material which plays a role in helping teachers explain lessons and students understand the material. Find out what is taught in the book "Basic Theory of Nahwu and Shorof Beginner Level Science" by Dr. H. Abdul Haris, M.Ag., is the first aim of this research. Find out how to convey the information in Dr. H. Abdul Haris, M.Ag. "Basic Theory of Nahwu and Shorof Science for Beginner Level" (3) To find out whether the teaching materials and methods in the book "Basic Theory of Nahwu & Sharf for Beginner Level" by Dr. H. Abdul Haris, M.Ag., can still be applied. Because the research source in this research is books, it is included in the library research category. To collect information from primary and secondary sources, content documentation techniques are used as a data collection method. In addition, non-statistical analysis or discourse analysis are two forms of data analysis methodology used in this research. The results of the research show that: (1) The teaching materials contained in the book "Basic Theory of Nahwu & Sharf for Beginner Level" are deemed inappropriate for students at the beginner level. The amount of information offered is too in-depth and complicated, making it unsuitable for beginners. (2) The book presentation strategy is considered quite good. This book discusses factors to consider when delivering content, including repetition, presentation, assessment, and selection. Also discussed is the use of life reflection expressions to motivate students. (3) The book "Basic Theory of Nahwu & Sharf Beginner Level" classifies the relationship between teaching content and presentation strategies as having a fairly good relationship, making it easier for students to understand the subject matter..